(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the issues of competence in organizing educational activities in elementary grades, pedagogical features of the expected results of the formation of spiritual education indicators, the state of the formation of professional competence of primary school teachers and the didactic abilities of primary school teachers.